DOES BUSINESS EDUCATION AFFECTS ENTREPRENEURIAL INTENTIONS? COMPARATIVE STUDY ON BUSINESS STUDENTS’ OCCUPATIONAL STATUS CHOICE (Case study of Mongolian University) - Batdelger, N.,; Delgerbuyan, G.,; Batsukh, N., (Journal of Business and Innovation (Бизнес & Инноваци), 2023)
Entrepreneurship education programs are to strengthen students’ management skills. We conducted the questionnaire survey about the attitude towards the self-employment (running own business). As a result, Business school’s students prefer to have their own business rather than employment in the organizations. Students who desire to have a job in organizations because of: (1) Social environment; (2) Stability (3) Career opportunity and students who desire to have a his/her own business because of: (1) Challenge; (2) Authority (3) Economic opportunity of running own business. From the comparative analysis, somehow business education affects the self-employment attitude during the study years in Business. We conclude some programs have influence the students’ self-employment attitude, and some haven’t influence that much.